Performance of Deltabeam–CLT Composite Floors Under Human-Induced Vibration - Huifeng Yang; Yushuang Wu; Benkai Shi; Haotian Tao; Haoyu Huang (Buildings, 2025)
In this study, the human-induced vibration performance of an innovative Deltabeam–CLT composite floor system was investigated. The Deltabeam–CLT composite floors were modelled using the finite element software package ABAQUS 6.14, the dynamic performance of the composite floors was evaluated, and the simulation results were benchmarked against prior simulation data in the other literature. In order to investigate the effect of the stiffness of Deltabeam composite steel beams on the vibration performance of Deltabeam–CLT composite floors, the acceleration of the Deltabeam–CLT composite floors under the excitation of a single person walking was measured. As per the acceleration, serviceability factors, namely, response factors (RFs) and vibration dose values (VDVs), were analyzed. The results showed that an increase in the height of Deltabeam composite steel beams can decrease the RF and VDV by 53.7% and 57.7%, respectively. This study also developed an optimization scheme with steel trusses pre-embedded inside Deltabeam composite steel beams. The effects of different truss spacing and rod diameters on the vibration performance of the Deltabeam–CLT composite floors were investigated; the results showed that the RF and VDV of Deltabeam–CLT composite floors can decrease to below 4 and 0.4 m/s−1.75, respectively, with a truss spacing smaller than 200 mm. These findings can significantly enhance the future design of the Deltabeam–CLT composite floor system, improving its serviceability and ensuring better performance in practical applications.